Attributing Vegetation Recovery During the Indian Summer Monsoon to Climate Drivers in Central India - Vikram Chandel; Tejasvi Chauhan (Ecology, Economy and Society – The INSEE Journal, 2023)
Increasing droughts and heat waves as a result of global warming pose a major threat to forests and croplands in India. Monitoring the dynamics of vegetation during a drought and its recovery is essential for the Indian socio-economy and biodiversity. We investigate vegetation recovery from a stressed state in the pre-monsoon (May) period to the end of the monsoon period (September). We then attribute net change during the monsoon period to climate drivers such as temperature, precipitation, and soil moisture. To delineate non-linear interactions, we use an information-theoretic metric to understand the relative association of climate variables with vegetation productivity on a daily scale. We found that pre-monsoon vegetation stress is influenced by soil moisture (r = 0.8, p < 0.01), which is driven by variations in temperature and precipitation. During the monsoons, precipitation contributes to vegetation recovery from pre-monsoon stress through soil moisture recharge while inhibiting vegetation productivity by limiting the amount of radiation available for photosynthesis. Linear regression shows the significant negative dependence of vegetation recovery on precipitation (β = –0.7, p < 0.01) and positive dependence on soil moisture (β = 0.4, p < 0.1) indicating radiation limitation on photosynthesis...